METODE KONSERVASI KOLEKSI NASKAH KUNO YANG DITERAPKAN PADA MUSEUM PROVINSI SULAWESI TENGGARA - Kafidah; Akhmad Marhadi; Salniwati Salniwati; Abdul Alim (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This research investigated the forms of conservation in ancient manuscript collections and the obstacles faced in conservation activities in ancient manuscript collections. The method used was qualitative with descriptive analitic model. Data collection in this research used documentation, observation and interviews .The research results show that forms of conservation in ancient manuscript collections in Southeast Sulawesi museums begin with carrying out periodic maintenance fumigation as needed using Silica Gel material. Fumigation is carried out 1 to 2 times a year. However, in this process there are several obstacles, namely, human resources in carrying out conservation of collections and ancient manuscripts so that it can only be done using silica gel, lack of facilities and infrastructure such as laboratories that are inadequate for forms of conservation of ancient manuscript collections.